2016
DOI: 10.1071/an15324
|View full text |Cite
|
Sign up to set email alerts
|

Managing the rumen to limit the incidence and severity of nitrite poisoning in nitrate-supplemented ruminants

Abstract: Inclusion of nitrate (NO3−) in ruminant diets is a means of increasing non-protein nitrogen intake while at the same time reducing emissions of enteric methane (CH4) and, in Australia, gaining carbon credits. Rumen microorganisms contain intracellular enzymes that use hydrogen (H2) released during fermentation to reduce NO3− to nitrite (NO2−), and then reduce the resulting NO2− to ammonia or gaseous intermediates such as nitrous oxide (N2O) and nitric oxide (NO). This diversion of H2 reduces CH4 formation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 84 publications
0
31
0
3
Order By: Relevance
“…Aschenbach et al (2009) reported that nitrate impaired acetate uptake through the rumen wall in vitro. Nolan et al (2016) suggested this to be a possible explanation for a shift in VFA profile towards acetate that has been reported upon nitrate supplementation, both in vitro and in vivo (Zhou et al, 2012;Guyader et al, , 2016de Raphélis-Soissan et al, 2016a). However, in the study of Aschenbach et al (2009) only acetate uptake was measured, and not uptake of propionate and butyrate.…”
Section: Additivitymentioning
confidence: 93%
See 4 more Smart Citations
“…Aschenbach et al (2009) reported that nitrate impaired acetate uptake through the rumen wall in vitro. Nolan et al (2016) suggested this to be a possible explanation for a shift in VFA profile towards acetate that has been reported upon nitrate supplementation, both in vitro and in vivo (Zhou et al, 2012;Guyader et al, , 2016de Raphélis-Soissan et al, 2016a). However, in the study of Aschenbach et al (2009) only acetate uptake was measured, and not uptake of propionate and butyrate.…”
Section: Additivitymentioning
confidence: 93%
“…As the VFA uptake mechanisms generally are not VFA specific, it is likely that nitrate will also have inhibited the uptake of other VFA, instead of being specific for acetate. Nolan et al (2016) showed that methemoglobin (MetHb) levels in sheep receiving a diet containing 2% nitrate remained constant and low (>12% of Hb) until 10 h after the first meal, when the diet was fed in hourly portions of 42 g. The MetHb levels in sheep receiving the same amount of feed (1 kg/d) not in hourly portions, but in either one or two meals per day, peaked during the hours after feeding. The authors discuss that the rate of nitrate reduction is increased when animals eat rapidly and/or when a feed restriction is applied.…”
Section: Additivitymentioning
confidence: 99%
See 3 more Smart Citations